2010
DOI: 10.1007/s11120-010-9529-9
|View full text |Cite
|
Sign up to set email alerts
|

Insights into heliobacterial photosynthesis and physiology from the genome of Heliobacterium modesticaldum

Abstract: The complete annotated genome sequence of Heliobacterium modesticaldum strain Ice1 provides our first glimpse into the genetic potential of the Heliobacteriaceae, a unique family of anoxygenic phototrophic bacteria. H. modesticaldum str. Ice1 is the first completely sequenced phototrophic representative of the Firmicutes, and heliobacteria are the only phototrophic members of this large bacterial phylum. The H. modesticaldum genome consists of a single 3.1-Mb circular chromosome with no plasmids. Of special in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Our studies showed that the anoxygenic heliobacterium Heliobacterium modesticaldum uses (Re)-citrate synthase ((Re)-CS), an alternative biosynthetic pathway, to produce citrate . Activity of (Si)-CS has not been detected and the gene encoding (Si)-CS has not been annotated in the H. modesticaldum genome (Sattley and Blankenship, 2009;Sattley et al, 2008). As indicated in Fig.…”
Section: (Re)-citrate Synthasementioning
confidence: 99%
“…Our studies showed that the anoxygenic heliobacterium Heliobacterium modesticaldum uses (Re)-citrate synthase ((Re)-CS), an alternative biosynthetic pathway, to produce citrate . Activity of (Si)-CS has not been detected and the gene encoding (Si)-CS has not been annotated in the H. modesticaldum genome (Sattley and Blankenship, 2009;Sattley et al, 2008). As indicated in Fig.…”
Section: (Re)-citrate Synthasementioning
confidence: 99%
“…Several features characterize the physiological and metabolic aspects of phototrophic heliobacteria [1-5]: (a) They are the only known phototrophs that belong to the gram-positive bacterial phylum Firmicutes , and as is typical of members of this group, which includes species of Bacillus and Clostridium , heliobacteria can form heat resistant endospores; (b) They produce the unique pigment bacteriochlorophyll g (BChl g ); (c) They produce 8 1 -hydroxy-chlorophyll a with a farnesol tail (8 1 -OH-Chl a F ), which serves as the primary electron acceptor from the reaction center (RC) special pair; (d) They contain a type I homodimeric RC bound to the cytoplasmic membrane; (e) They require organic carbon sources for both phototrophic growth and chemotrophic (fermentative) growth; and (f) they are active nitrogen-fixers and also produce hydrogen. Further, Heliobacterium modesticaldum , isolated from hot springs microbial mats and volcanic soils in Iceland [6], is one of only two known anoxygenic phototrophs that can fix nitrogen at temperatures higher than 50°C (the other is Chlorobaculum tepidum ) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the cytoplasmic membrane is the only membrane system found in Heliobacteria [48]. All membrane-bound complexes, including all photosynthetic complexes and a large number of various transporters for transporting essential substrates into the cells, are confined to this cytoplasmic membrane [2, 48]. According to the complete genome sequence analysis of H. modesticaldum [49], a gene cluster was identified for the ATP synthase that contains all eight subunits and it is assumed that the enzyme is present in the cytoplasmic membrane [2, 49].…”
Section: Resultsmentioning
confidence: 99%
“…Heliobacterium modesticaldum is a thermophilic anoxygenic phototrophic bacterium that grows either photoheterotrophically or chemotrophically in the dark by fermentation but does not grow photoautotrophically due to the lack of several genes encoding key enzymes required for the known autotrophic carbon fixation pathways [1, 2]. Heliobacterium modesticaldum may have played a key role in the evolution of phototrophic bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation